Developing Kopaja.id as a fun online learning in general tax conditions topic - Rumiyati Rumiyati; Dianila Oktyawati (Jurnal Pendidikan Vokasi, 2020)
Kopaja.id as online learning had developed in 2019, and KOPAJA is an acronym for "Kompas Pajak Ajaib" which means magically direct taxes. It is also expected to provide a fun learning for students. This research is to provide an online fun learning to students who want to learn tax anytime and anywhere. This research is follow-up research using the research and development (R&D) method to reach the Technology Readiness Level (TRL) for applied research. The development of an application system has been carried out based on a website with the address https://kopaja.id which can be accessed and used for learning from taxation courses. User testing with the Perceived Usability Website instrument was developed by Wang and Senecal. The research sample is from 55 students of DIV Public Sector Accounting, Department of Economics and Business, Vocational College, Universitas Gadjah Mada. The test results show that the website system is functioning correctly, and user ratings show that the website has easy navigation, speed of access, and is comfortable to explore. However, interaction with users is still not optimal. The result of self-measurement on the achievement of Technology Readiness Level reaches TRL 6 in 1- 9 scale.